Metronidazole therapy as initial treatment of Clostridium difficile infection in patients with chronic kidney disease in Korea. (2019) - Shin, Jaeuk; Wi, Yu Mi; Lee, Yu-Ji
Abstract: The risk of metronidazole treatment failure in Clostridium difficile infection (CDI) patients with chronic kidney disease (CKD) or end-stage renal disease in Korea has not been established. We evaluated 481 patients who had been admitted to two secondary hospitals with a diagnosis of, and treatment for, CDI during 2010–2016. CDI patients were divided into three groups according to CKD status: non-CKD ( n = 363), CKD ( n = 55) and those requiring dialysis ( n = 63). Logistic regression analyses were performed to examine the association of CKD status with treatment failure. CDI patients receiving dialysis tended to have increased odds of metronidazole and overall treatment failure compared to non-CKD patients; adjusted odds ratios and 95% confidence intervals were 2.09 (1.03–4.21) and 2.18 (1.11–4.32) for metronidazole and overall treatment failure, respectively. However, CKD patients did not have increased odds of metronidazole or overall treatment failure compared to non-CKD patients, even where severe CDI was more prevalent in CKD patients. The incidence of symptomatic ileus or toxic megacolon did not differ among groups. Our results suggest that initial metronidazole therapy may be considered in CDI patients with non-dialysis CKD, but should not be considered in CDI patients undergoing dialysis.